Retrospective evaluation of combined modality treatment and prognostic factors in patients with esophageal cancer - Neuhof, Dirk; Neumayer, Florian; Einbeck, Wolfgang; Haschemian, Kai; Mai, Sabine; Hochhaus, Andreas; Willeke, Frank; Rudi, Jochen; Debus, Jürgen; Wenz, Frederik (Acta oncologica, 2005)
The influence of prognostic factors and combined modality treatment on survival was evaluated retrospectively for 156 patients with esophageal cancer receiving radiotherapy in different modalities between 1991 and 2001 at the University of Heidelberg and the Universitatsklinikum Mannheim. Forty- six patients ( 29.5%) were treated with radiotherapy alone, 74 patients ( 47.4%) had combined radiochemotherapy and 36 patients ( 23.1%) were operated on after receiving neoadjuvant radiochemotherapy. The median follow- up time was 10 months. Female patients showed a significantly better overall survival compared with male patients ( p = 0.031), younger patients ( age <= 60 years) a significantly better survival compared to older patients ( age > 60 years) ( p = 0.02). Patients with hemoglobin concentration > 13.4 g/ dl before therapy ( median hemoglobin concentration) had a significantly better overall survival than patients with lower hemoglobin concentration ( p = 0.044). Patients who received combined radiochemotherapy ( with or without operation) had a survival advantage compared with radiotherapy alone. Overall survival after neoadjuvant treatment followed by operation was significantly better than in the two other groups, median survival times were 20 vs. 9 ( RCHT) vs. 8 months ( RT) ( p = 0.003). The data presented show for the first time that hemoglobin concentration in addition to gender and age was a prognostic factor for patients with esophageal cancer. A low hemoglobin value was a negative predictor.